Analisis Kemampuan Literasi Matematis Siswa Ditinjau Dari Karakter Kemandirian Belajar Materi Aljabar - Kholifasari, Rizqi; Utami, Citra; Mariyam, Mariyam (Pendidikan Matematika Universitas PGRI Yogyakarta, 2020)
This study aims to: 1) describe students' mathematical literacy skills in algebraic material in terms of learning independence. 2) to describe the factors that affect students' mathematical literacy skills in algebraic material in terms of learning independence. This research method is qualitative. The subjects in this study were students of class VIII-A at SMP Negeri 1 Singkawang. The data collection instruments used a learning independence questionnaire, a mathematical literacy test, and an interview sheet. Data analysis techniques used the Miles and Huberman Model, namely, data reduction, data presentation, and drawing conclusions. The results showed that 1) The students' mathematical literacy ability in terms of their high learning independence character had an average of 69.44 (high category). Most of the students were unable to do the reasoning and argumentation stages. 2) The students' mathematical literacy skills in terms of their moderate learning independence character had an average of 57.41 (moderate category). Most of them were unable to develop strategies for solving problems. 3) The students' mathematical literacy ability in terms of their low learning independence character has an average of 46.11 (moderate category). Most of them are not capable at the mathemathising stage. 4) factors that affect mathematical literacy skills in terms of the character of independent learning in algebra material are generally influenced by internal factors, namely factors from the students themselves, students are less able to understand, accept, or digest subject matter, students have difficulty planning strategies in problem solving both in using the formula to be used, the rules in operation, do not provide the right steps in answering the questions.Keywords: mathematical literacy skills, learning independence